3. Pengujian validitas lembar kerja siwa (LKS) berbasis problem solving dalam mencapai keterampilan berpikir kritis pada materi gelombang untuk kelas XI SMA/MA - Ully Nuraidina; yenni darvina; wahyuni satria dewi (PILLAR OF PHYSICS EDUCATION, 2019)
The 2013 curriculum requires that physics learning be carried out completely and well using a variety of learning resources. The reality in physics learning schools has not been implemented properly, teachers have not fully implemented the learning process using problem solving learning models, teachers have not used worksheets that are in accordance with the 2013 curriculum and the integration of 21st century skills students have not been fully implemented, especially critical thinking skills. One solution to this problem is to create a problem solving worksheet based on achieving critical thinking skills. The purpose of this study is to produce worksheet based on valid and practical problem solving. Research conducted includes the type of Research and Development (R&D). The object of this research is the Problem Solving Based Worksheet on wave material. The steps of this research are six stages, starting from recognizing potentials and problems, gathering information, designing products, validating products, revising products and to testing products with limited testing. The tools to collect data are validity sheets from experts and practicality sheets from physics subject teachers, as well as practicality sheets from class XI students of SMAN 3 Pariaman. The data analysis technique used is descriptive statistical analysis for product validation and clarity. Based on data analysis from the research that has been done can be presented two research results. First, the worksheet based problem solving in wave material is very valid with an average value of validity of 88.45. Second, worksheet based problem solving on wave material is very practical with an average value of practicality of teachers and students of 88 and 89.44. So, it can be concluded that the worksheet based on problem solving in class XI wave material SMA / MA is very valid and very practical.